2004
DOI: 10.1161/01.cir.0000145123.85083.66
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Vascular Endothelial Growth Factor Suppresses Experimental Restenosis After Intraluminal Injury by Inhibiting Recruitment of Monocyte Lineage Cells

Abstract: Background— Therapeutic angiogenesis by delivery of vascular endothelial growth factor (VEGF) has attracted attention. However, the role and function of VEGF in experimental restenosis (neointimal formation) after vascular intraluminal injury have not been addressed. Methods and Results— We report herein that blockade of VEGF by soluble VEGF receptor 1 ( sFlt-1 ) gene transfer attenuated n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 37 publications
4
104
0
3
Order By: Relevance
“…Emerging evidence indicates that VEGF plays a critical role in host inflammatory responses in several disease states, including atherosclerosis (7,12,18,21,23,25,39,40), sepsis (37), acute lung injury (15), and rheumatoid arthritis (11). These data indicate that besides the proangiogenic activity, VEGF has a potent proinflammatory property, although the underlying mechanism is largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates that VEGF plays a critical role in host inflammatory responses in several disease states, including atherosclerosis (7,12,18,21,23,25,39,40), sepsis (37), acute lung injury (15), and rheumatoid arthritis (11). These data indicate that besides the proangiogenic activity, VEGF has a potent proinflammatory property, although the underlying mechanism is largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, inhibition of growth factor signaling reduced it. [78][79][80] Microcomputed tomography imaging further demonstrates a direct correlation between the computed tomography-determined extent of adventitial angiogenesis and the extent of neointima. 19,81 Thus, there is a strong correlation between the extent of the adventitial vasculature and the extent of neointima formation.…”
Section: Vasa Vasorum and Neointima Formationmentioning
confidence: 99%
“…Therefore, VEGF can circulate in a bound state (bound to sFlt-1) as well as in free state depending on the amount of sFlt-1 in the circulation. In this regard, several reports have suggested that sFlt-1 can serve as an antitumor agent by inhibiting VEGF (130)(131)(132). The relevance for sFlt-1 at the normal physiologic concentration in the regulation of cancer progression is not understood.…”
Section: Non-matrix-derived Inhibitors Of Angiogenesismentioning
confidence: 99%